Effect of Hydrogen Peroxide Addition Method on Fenton Oxidation of Sugarcane Vinasse - Nindia Noor Indah; Riezky Gusti Fadhlillah; Amani Salsabil Husodo (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2026)
Vinasse, a highly polluting byproduct generated during ethanol production, exhibited a very high chemical oxygen demand (COD) of 132,000 mg/L, making its treatment a critical environmental challenge. To reduce COD levels in vinasse, the Fenton process was employed in this study. The experiments were carried out for 1 hour in batches at atmospheric pressure and ambient temperature. The chemical reagents used for the reaction consisted of a 50% H₂O₂ solution and Fe(NO₃)₃·9H₂O, with the key variable being the H₂O₂ addition method of direct addition (one-shot, 80 mL at t=0) and stepwise (gradually, 20 mL aliquots at t=0, 10, 20, 30 min). Samples were collected every 10 minutes for COD analysis. While both dosing methods demonstrated time-dependent COD removal, the stepwise addition proved to be significantly more efficient, achieving a maximum measured removal of 57.39% compared to 39.12% for the direct H2O2 addition method. Furthermore, biphasic kinetic modeling showed that the direct addition of H₂O₂ exhibited a rapid initial oxidation phase (k1=0.0925 min⁻¹) followed by a slower and almost stagnant phase (k2=0.0005 min⁻¹). In contrast, the stepwise addition resulted in a lower but more sustained degradation rate (k1=0.0246 min⁻¹; k2≈0 min⁻¹), indicating a more uniform oxidation behavior under stepwise oxidant loading.